Freedom of poking fun - Abd Razak, Dzulkifli (2010)
The Facebookbased competition, Everyone Draw Mohammed (sic) Day!, on May 20 is said to promote "freedom of expression". It brings to mind a talk that I attended on the eve of the day in Penang. The speaker was retired Captain James Yee, who acted as US Army chaplain at Guantanamo Bay, Cuba in 2001.